A Systematic Review of Right Ventricular Diastolic Assessment by 4D Flow CMR. (14th March 2019) - Barker, Natasha; Fidock, Benjamin; Johns, Christopher S.; Kaur, Harjinder; Archer, Gareth; Rajaram, Smitha; Hill, Catherine; Thomas, Steven; Karunasaagarar, Kavitasagary; Capener, David; Al-Mohammad, Abdullah; Rothman, Alexander; et al.
Abstract : Background . Four-dimensional flow cardiovascular magnetic resonance (4D flow CMR) is a noninvasive novel imaging technology that can be used to visualise and assess right ventricular function. The aim of this systematic review is to summarise the literature available on 4D flow CMR methods used to determine right ventricular diastolic function. Methods . A systematic review of current literature was carried out to ascertain what is known about right ventricular assessment by quantification of 4D flow CMR. Structured searches were carried out on Medline and EMBASE in December 2018. PG and NB screened the titles and abstracts for relevance. Results . Of the 20 articles screened, 5 studies met eligibility for systematic review. After a further search on pubmed 1 more relevant article was found and added to the review. Conclusions . These proposed methods using 4D flow CMR can quantify right ventricular diastolic assessment. The evidence gathered is mainly observational, featuring single-centred studies. Larger, multicentre studies are required to validate the proposed techniques, evaluate reproducibility, and investigate the clinical applicability that 4D flow CMR offers compared to standard practices. PROSPERO registration number isCRD42019121492 .